Three Fallacies, Three Reminders, and Three Exhortations: The Chiastic Structure of 1 Corinthians 6:12–20 - Na, Jooman (The Evangelical quarterly, 2025)
This study demonstrates the chiastic structure of 1 Corinthians 6:12-20 and Paul’s rhetorical strategy through an exegetical analysis of the passage. The argument unfolds in two movements: the first half (vv. 12-14) presents the Corinthians’ fallacies regarding freedom, the body, and resurrection, while the second half (vv. 15-20) recalls what they already knew—their union with Christ, the body’s purpose, and its status as the temple of the Holy Spirit—each joined with an exhortation. The repeated phrase ‘do you not know’ provides internal markers that reinforce this arrangement. This chiastic structure shows how Paul pairs ignorance with knowledge, fallacy with reminder, so that his exhortations emerge with persuasive force. Recognizing this structure not only clarifies the coherence of the passage but also highlights Paul’s theological logic and pastoral strategy, contributing to ongoing discussions of the internal structure of 1 Corinthians 6:12-20.